The Political Marketing Game - Lees-Marshment, J. author. aut Link
XV, 259 p.
Keywords: The Political Marketing Game identifies what works in political marketing, drawing on 100 interviews with practitioners. It also shows that authenticity, values and vision are as much a part of a winning strategy as market-savvy pragmatism.